The Role of the Family Environment in Children's Learning Motivation in Underprivileged Communities - Feby Nuralia; Ilwinda Meiriski Aulia; Zahra Juandari; Rika Fitri Rahmadani (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to analyze the influence of family environment on children’s learning motivation in underprivileged communities. The family environment is the primary factor affecting children’s psychological development and learning enthusiasm, particularly under economically constrained conditions. This research employed a descriptive qualitative approach, with data collected through in-depth observation, interviews, and documentation. Research subjects were school-age children (7–15 years old) and their parents from low-income families. Data analysis followed three stages: data reduction, data display, and conclusion drawing, supported by source and technique triangulation to ensure data credibility. The findings reveal that low economic conditions, limited parental education, and unsupportive parenting styles are the main inhibiting factors of children’s learning motivation. However, emotional support, parental attention, and warm communication within the family were proven to significantly enhance children’s learning motivation despite economic limitations. These findings align with motivation theory and Bronfenbrenner’s ecological theory of human development, which emphasize the role of the family microsystem in shaping children’s intrinsic motivation. Therefore, strengthening family capacity through parental assistance programs is the primary recommendation of this study.